Thyrotoxic neuropathy - a case report (Indian Journal of Case Reports, 2019)
Thyrotoxic neuropathy is a rare entity in literature. The association between thyrotoxicosis and neuropathy is under-recognized. We here present a rare case report in which patient was presented with ascending sensory-motor paralysis coupled with respiratory muscle weakness which closely resembles Guillain–Barré syndrome (GBS). But relevant history suggested thyrotoxic features, thus a timely focused investigation revealed the diagnosis. It was confirmed in nerve conduction studies (NCS) and other necessary investigations ruled out other differential diagnosis. Patient was treated with anti-thyroid drugs. On follow up patient’s power improved and NCS after 6 months came out to be normal which established the diagnosis. Thyrotoxic neuropathy is a close differential diagnosis of LGBS and other commonly encountered neuroparalytic illnesses. So high degree of suspicion is needed to diagnose this potentially treatable neuropathy.